2022
DOI: 10.1021/acs.biochem.2c00354
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Phosphate and Ferritin Subunit Composition on the Kinetics, Structure, and Reactivity of the Iron Core in Human Homo- and Heteropolymer Ferritins

Abstract: Ferritins are highly conserved supramolecular protein nanostructures that play a key role in iron homeostasis. Thousands of iron atoms can be stored inside their hollow cavity as a hydrated ferric oxyhydroxide mineral. Although phosphate associates with the ferritin iron nanoparticles, the effect of physiological concentrations on the kinetics, structure, and reactivity of ferritin iron cores has not yet been explored. Here, the iron loading and mobilization kinetics were studied in the presence of 1–10 mM pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…One stimulating possibility for the lower thermal stability of holo‐ferritin is that the iron nanoparticles inside the protein could accelerate/facilitate heat transfer from the iron core to the protein moiety leading to protein structural changes or protein damage. Additionally, the observed thermal stability difference between H and L ferritins may be due to different iron core structures or morphologies (Reutovich et al, 2022) with different heat capacities. Although earlier studies have showed that ferritin iron core can be heated by physical stimulations such as microwaves or magnetic fields, a recent study (Meister, 2016) debunked the idea that ferritin iron cores can be heated by magnetic fields.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One stimulating possibility for the lower thermal stability of holo‐ferritin is that the iron nanoparticles inside the protein could accelerate/facilitate heat transfer from the iron core to the protein moiety leading to protein structural changes or protein damage. Additionally, the observed thermal stability difference between H and L ferritins may be due to different iron core structures or morphologies (Reutovich et al, 2022) with different heat capacities. Although earlier studies have showed that ferritin iron core can be heated by physical stimulations such as microwaves or magnetic fields, a recent study (Meister, 2016) debunked the idea that ferritin iron cores can be heated by magnetic fields.…”
Section: Discussionmentioning
confidence: 99%
“…One relevant interpretation for the lower stability of holo-ferritin is that an iron-loaded ferritin could be "sensed" in vivo and primed for degradation and iron recycling. It is possible that endogenous iron loading into ferritin follows an entirely different mechanism than exogenous iron loading, even though the end product is an iron-loaded ferritin (Reutovich et al, 2022). Interestingly, the half-life of ferritin in rat liver was reported to be about 2.5 days (Vulimiri et al, 1977), but in cell culture, the half-life can be as short as 3.5 h (Mehlhase et al, 2005), suggesting that the significant differences between the two environments lead to different processes of ferritin degradation and iron re-cycling.…”
Section: Effect Of Iron Loading On Ferritin's Structure and Stabilitymentioning
confidence: 99%
“…Additionally, the crystallinity of the mineral core has been shown to be related to the phosphate content of the iron core, varying from amorphous in plants and microbial ferritins having Fe:P ratio of ∼1:1 to nanocrystalline in animal ferritins with Fe:P of ∼8:1 [ 18 , [48] , [49] , [50] , [51] , [52] ]. A recent study from our laboratory employing spectroscopy and scanning transmission electron microscopy (STEM) revealed striking differences in the iron oxidation and mobilization kinetics and the resulting morphologies of the iron core; recombinant L-rich human ferritin exhibits spherical iron core morphologies whereas recombinant H-rich human ferritin showed more irregular core morphologies with rod and crescent like features [ 53 ], suggesting that the structure of the iron mineral may have a profound impact on the iron core reactivity with important implication on ferritin iron management in vivo.…”
Section: Structural/functional Thermostability and Self-assembly Prop...mentioning
confidence: 99%
“…Recombinant human L ferritins were expressed using pDS 20 vectors with ampicillin resistance and transformed into BL21 pLyS strain using M9 minimal medium for 7 h at 37 °C. Recombinant human heteropolymer ferritins with different H to L subunit ratios were produced in E. coli Rosetta-gami B strain using a recently engineered pWUR-FtH-TetO-FtL plasmid and different concentrations of inducers, as described in detail elsewhere 24,26 . Transformed cells were induced at 37 °C for 4-6 h using 10-1000 μM isopropyl β-D-1-thiogalactopyranoside (IPTG from Sigma Aldrich), 25-1600 ng/ml of anhydrotetracycline (IBA solutions).…”
Section: Recombinant Ferritin Expression and Purificationmentioning
confidence: 99%
“…Nonetheless, the results of these studies have shown that heteropolymer ferritins have properties that differ significantly from homopolymers 5 . To address this shortcoming, we have engineered a novel ferritin expression system to produce recombinant heteropolymer ferritins with different H to L subunit ratios that mimic those found in various organs and tissues 24 , have characterized their iron uptake and release kinetics, and the structure and morphologies of their iron cores [25][26][27][28] . Our unique plasmid design allowed the synthesis of a full spectrum of heteropolymer ferritins, from H-rich to L-rich ferritins and any combinations in-between, enabling us for the first time to examine structural and functional differences of isoferritin populations [24][25][26][27][28] .…”
mentioning
confidence: 99%